Going Digital : Credit Effects of Land Registry Computerization in India - Deininger, Klaus; Goyal, Aparajita (2012)
Despite strong beliefs that property titling and registration will enhance credit access, empirical evidence in support of such effects remains scant. The gradual roll-out of computerization of land registry systems across Andhra Pradesh's 387 sub-registry offices allows us to combine quarterly administrative data on credit disbursed by all commercial banks for an eleven-year period (1997-2007) aggregated to the sub-registry office level with the date of shifting registration from manual to digital. Computerization had no credit effect in rural areas but led to increased credit-supply in urban ones. A marked increase of registered urban mortgages due to computerization supports the robustness of the result. At the same time, estimated impacts from reduction of the stamp duty are much larger, suggesting that, without further changes in the property rights system, impacts of computerization will remain marginal.